Sistem Informasi Pengarsipan Data Penduduk DP3A Kabupaten Nabire Berbasis Web - Gloriyana Dwijayanti Hurulean; Kristia Yuliawan (STMIK Pesat Nabire, 2026)
Efficient and accurate management of population data is a crucial aspect for government organizations, especially the Nabire Regency Women's Empowerment and Child Protection Office (DP3A). Currently, manual filing methods cause various obstacles, such as data errors, delays in public services, and difficulties in the reporting process. This study proposes the development of a web-based population data archiving information system using the Waterfall method. The system is designed to integrate and automate the process of managing sensitive data, including search, update, and report generation features. The results of the development show that the system is able to improve operational efficiency, data accuracy, and information security. In addition, this system supports transparency and accountability in the management of the DP3A program, including MSME and Family Planning data, while facilitating access to information for the public. Thus, this web-based archiving information system is expected to be a strategic solution in improving the quality of public services and supporting more appropriate decision-making within the DP3A environment of Nabire Regency.